Physicochemical, textural, and microstructural properties of kenaf (Hibiscus cannabinus L.) seed tofu as affected by coagulant types and concentrations - Ibrahim, S.G.; Wan Makazan, W.F.N.; Karim, R. (Universiti Putra Malaysia, 2024)
Hard tofu was developed from kenaf seed, and the effects of coagulant types and concentrations on the physicochemical, textural, and microstructural properties of the tofu were studied. Glucono delta-lactone (GDL), CH3COOH, MgCl2, and CaSO4 were the coagulants used at concentrations of 0.25, 0.5, 0.75, and 1.0 g% (w/v). Kenaf seed milky extract was obtained from the seed soaked at 65°C for 2 h 40 min, and ground using 1:6 seed-to-water ratio. The extracted milky extract was cooked to 95°C for 3 min, cooled to 80°C, and then coagulated with appropriate coagulant concentration. The yield, physicochemical, texture, and microstructure of the tofu were examined. The results indicated that the yield and moisture content of the tofu were not significantly affected by coagulant types and concentrations. Coagulant types affected the crude protein, crude fat, and surface colour of the tofu. GDL-coagulated tofu had significantly higher crude protein (35.09 - 39.07 g/100 g), while MgCl2-coagulated tofu had significantly higher crude fat (59.64 - 63.15 g/100 g). The hardness, chewiness, and springiness of the tofu were affected by the coagulant types and concentrations. CH3COOH-coagulated tofu had significantly higher hardness (2490.1 - 4005.8 g), while MgCl2-coagulated tofu had significantly lower hardness (814.45 - 2009.9 g). Scanning electron microscopy of all the tofu showed a rough-like structure of denser aggregated proteins with large pores, except for the tofu made with 0.25 g% (w/v) which exhibited a pseudo-honey-like structure of compacted network strands. It was concluded that all the coagulants at 0.25 g% (w/v) were suitable to produce kenaf seed tofu.